2016
DOI: 10.4046/trd.2016.79.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A1 Inhibits TGF-β1–Induced Epithelial-to-Mesenchymal Transition of Alveolar Epithelial Cells

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive and lethal lung disease characterized by the accumulation of excessive fibroblasts and myofibroblasts in the extracellular matrix. The transforming growth factor β1 (TGF-β1)–induced epithelial-to-mesenchymal transition (EMT) is thought to be a possible source of fibroblasts/myofibroblasts in IPF lungs. We have previously reported that apolipoprotein A1 (ApoA1) has anti-fibrotic activity in experimental lung fibrosis. In this study, we determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…15 TGF-β1 induced nonSmad responses, including extracellular signal-regulated kinase (ERK) and p38 mitogen-activated protein kinase (p38 MAPK) mediated signaling. 16 The present study mainly explores the nonSmad signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 TGF-β1 induced nonSmad responses, including extracellular signal-regulated kinase (ERK) and p38 mitogen-activated protein kinase (p38 MAPK) mediated signaling. 16 The present study mainly explores the nonSmad signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…18 For mammals, members of the MAPKs superfamily mainly include the ERK, p38 MAPK, and c-JUN, NH2-terminal protein kinase (JNK). 19 Although study has shown that MAPK signaling pathway could be activated in the signal transduction of the TGF-β1-induced pulmonary fibrosis, 16 it still have differences between species and cell types. 20,21 ECM deposition is one of the mechanisms in pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial-to-mesenchymal transition (EMT) plays a critical role in driving cancer cell metastasis 8 , 9 . Transforming growth factor β (TGF-β1) is the driver of EMT, and many influencing factors promote EMT through this signaling pathway 10 , 11 . Recently, several reports revealed that lncRNA Metastasis-Associated Lung Adenocarcinoma Transcript 1 (MALAT1) has crucial functions in malignant cancer progression 12 .…”
Section: Introductionmentioning
confidence: 99%
“…To induce EndMT, the cells were stimulated for 48 h in serum-free medium (SFM) with 0.1% bovine serum albumin (BSA) and TGF-β1 (10 ng/mL, R&D Systems, Minneapolis, MN, USA). To evaluate the effect of ApoA-I on the TGF-β1-induced EndMT, the culture medium was replaced with SFM supplemented with 0.1% BSA, TGF-β1 (10 ng/mL) and recombinant human ApoA-I (50 ng/mL, Calbiochem, San Diego, CA, USA), and the cells were incubated for 48 h. Control cells were maintained in SFM with 0.1% BSA for 48 h [16]. Cells were cultured in a humidified 5% CO 2 incubator at 37°C and used between the fourth and sixth passages.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, studies have demonstrated that ApoA-I can inhibit the oxidation of low-density lipoprotein (LDL), damage to the endothelium, and the transformation of macrophages to foam cells [11,12,13,14,15]. Recently, ApoA-I has been found to have an inhibitory effect on the TGF-β1-induced epithelial-to-mesenchymal transition of alveolar epithelial cells [16]. In addition, it has recently been reported that HDL reduces TGF-β1-induced EndMT in human aortic ECs [17].…”
Section: Introductionmentioning
confidence: 99%